Municipios y construcción democrática en Cuba - Haroldo Dilla Alfonso (Perfiles Latinoamericanos, 1996)
The Cuban municipal system created in 1976 has coped satisfactorily with tasks related to regional development, the carrying out of public policies and the creation of democratic spaces. At the same time, the municipalities have suffered serious shortcomings, be it because of the weaknesses of their institutional design or because of the systemic milieu in which they have acted. The economic changes experienced in Cuba since 1989 raise new challenges for the municipalities with regards the allocation and distribution of resources, the expression of demands and conciliation of interests in local societies with are becoming more complex and contradictory. This points to the need for institutional and normative redesigning, in order to potentiate popular participative spaces and representative organs as a function of an extension of democracy.